2018
DOI: 10.14419/ijet.v7i4.15.21439
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review: Risk Factors of Low Back Pain in Military Personnel/Recruits

Abstract: Military personnel are one of the occupations at high risk of developing low back pain (LBP) due to its job demands. Low back pain (LBP) is a major cause of morbidity and lost from work among military personnel. This narrative review was conducted to determine the risk factors of LBP in military personnel/recruits. Searches focusing on causal comparative and epidemiology studies using OVIDMedline, CINAHL, SPORTDiscus, PubMed, and Scopus databases from year January 1950 to April 2018. The Preferred Reporting It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…CLBP is a multifactorial disorder, and previous studies have confirmed the roles of individual factors, health behaviors, work organization, psychosocial, and biomechanical (occupational) risk factors in the back pain onset and its exacerbation [4,5,10]. Overall, the LBP-related risk factors in Army personnel are categorized as individual, psychosocial, and occupational risk factors [3]. Despite the critical role of the individual and psychosocial factors in developing LBP, Army personnel are at high risk of developing LBP due to job demands [3].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…CLBP is a multifactorial disorder, and previous studies have confirmed the roles of individual factors, health behaviors, work organization, psychosocial, and biomechanical (occupational) risk factors in the back pain onset and its exacerbation [4,5,10]. Overall, the LBP-related risk factors in Army personnel are categorized as individual, psychosocial, and occupational risk factors [3]. Despite the critical role of the individual and psychosocial factors in developing LBP, Army personnel are at high risk of developing LBP due to job demands [3].…”
Section: Introductionmentioning
confidence: 98%
“…Low back pain (LBP) is the most common disorder among Army personnel, defined as pain localized below the costal margin and above the inferior gluteal folds, with or without leg pain [1][2][3]. LBP impacts troop readiness and leads to ambulatory care, work duty limitation, lost days, and disability in the Armed forces [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Army personnel have a high risk of developing LBP due to the demands of the job. The findings of narrative review by Waqqash et al [20] revealed that army personnel have high occupational physical exposure as their job scope requires usage of heavy body armour for a prolonged duration, heavy carrying and lifting, standing and marching for a long duration, and undergoing rigorous physical and combat training. According to Roy et al [16], the relative risk rates for LBP identified among army personnel are: (1) wearing a load more than 10% BW (RR = 2.00, 1.31-4.57), (2) wearing an average load for more than 1 hour (RR = 2.44, 1.30-4.57), (3) load worn more than 15% BW (RR = 5.83, 1.51-22.50), (4) wearing a backpack (RR = 1.82, 1.23-2.80), (5) wearing body armour >1 hour (RR = 1.62, 1.002-2.62), (6) Lifting objects weighing above 22.68 kg (RR = 1.96, 1.08-3.57), (7) Lifting objects one to two times (RR = 1.73, 1.002-2.97), and (8) carrying objects more than 7.62 m (RR = 2.01, 1.19-3.42).…”
Section: Introductionmentioning
confidence: 99%